Anthropometric labial analysis of Han Chinese young adults. Issue 4 (13th February 2019) - Wang, Yan; Guo, Shu; Sun, Qiang; Jin, Shi‐feng; Zhang, Xin; Xiao, Ming; Wang, Chen‐chao; Sun, Xu; Lv, Meng‐zhu; Li, Ke‐zhu
Abstract: Background: Facial features vary in size and proportions between different races. This study aimed to measure the anthropometric variables of the labial region in Han Chinese young adults. Materials and Methods: A total of 900 college students (475 male and 425 female) of Chinese Han ethnicity from the northern China were included. Measurements of the labial region included 14 linear items and seven proportions. Results: All the linear measurements of the males were significantly higher than those of the females (all P  < 0.001). Significant gender differences were found in the philtrum morphology, philtrum width, upper vermilion‐cutaneous lip, lower vermilion‐cutaneous lip, and vermilion. There are significant differences in the anthropometric variables of the labial region between male and female Han Chinese young adults. Conclusions: These data may be used as a reference standard for labial reconstructive and aesthetic surgery.